Implementasi Nilai Pendidikan Karakter Dalam Cerita Bhagawan Domya - Desak Nyoman Sri Suyasning Putri (Jayapangus Press, 2019)
The many phenomena that occur in the community and in the world of education are related to one's attitude in the era of globalization which tends to decrease the value of morality and character education of Hinduism which is indicated by reduced honesty, hard work, devotion to the teacher and parents, it is deemed necessary to apply the value of character education. As a non-formal school, Pasraman is a place or place for Hindu students to develop the values ​​of character education in improving ethics and morals in accordance with the teachings of Hinduism, guided by Hindu literature, one of which is the story of Bhagawan Domya. The issues to be discussed include: (1) What character education values ​​are contained in Bhagawan Domya's story? (2) How is the implementation of character education in the story of Bhagawan Domya in Pasraman Ḉradha Wrdhi Bhakti Desa Pakraman Pengosekan? (3) What are the implications of the application of character education values ​​in the story of Bhagawan Domya in Pasraman Ḉradha Wrdhi Bhakti Desa Pakraman Pengosekan? This study aims (1) to determine the value of character education contained in the Bhagawan Domya Story, (2) To determine the implementation of character education values ​​in the story of Bhagawan Domya in Pasraman Ḉradha Wrdhi Bhakti Pakraman Pengosekan Village,, (3) To find out the implications of the application of Value of Education Character in the Story of Bhagawan Domya in Pasraman Ḉradha Wrdhi Bhakti Desa Pakraman Pengosekan. The theory used to analyze problems is: Value theory from Koentjaraningrat, Constructivism theory from Jean Paiget, the theory of Stimulation of Reply from Daryl Beum. The subject of this research was sisya Pasraman Ḉradha Wrdhi Bhakti Desa Pakraman Pengosekan. Data collection methods are participant observation, unstructured but in-depth interviews and literature. The data that has been collected is analyzed with qualitative descriptive analysis methods with steps of reduction, data presentation, and conclusion drawing. The results showed, (1) The value of character education in Bhagawan Domya's story are: religious character, honesty, discipline, hard work, creative, independent, respectful achievement, social care and responsibility. (2) The implementation of character education values ​​in the story of Bhagawan Domya in Pasraman Sharadha Wrdhi Bhakti Pengosekan, Ubud, Gianyar Regency, namely: The application of religious character, the application of honest characters, the application of disciplinary characters, the application of hard work characters, the application of character Creative, The existence of the application of Independent Characters, the application of Characters Appreciating Achievement, The Application of Social Care Characters, the Application of Character Responsibility (3) Implications of Character Education in the Bhagawan Domya Story in Pasraman Ḉradha Wrdhi Bhakti Pengosekan is an Implication of spiritual attitudes, implications towards knowledge and implications for skills.